Template-free aqueous tape casting of hydrothermally synthesized barium titanate powder and the fabrication of highly 001-100 textured tapes. Issue 8 (1st June 2018) - Özen, Murat; Mertens, Myrjam; Snijkers, Frans; Cool, Pegie
Abstract: Aqueous slurries of hydrothermally prepared barium titanate (BaTiO3 ) powders were tape casted without the use of large anisotropic template materials. The tapes were sintered at 1400 °C or 1500 °C, and at different furnace parameters. The texture of the sintered tapes was evaluated by the semi-quantitative XRD Lotgering method and the microstructure was studied by SEM. The Lotgering factor ( f ) of the sintered tapes was positively influenced by two main variables. First, directly heating to the sintering temperature resulted in a 22–30% increase. Second, sintering in the liquid-phase (Ti-excess) temperature region and at a high enough temperature (1500 °C) drastically improved the relative intensity of the 100 and 001 lines by 72%, at the expense of the 101- and 111-lines. The average volume weighted grain-size of the tape, which was directly heated to the sintering temperature (i.e., skipping the calcination step), was decreased by 77%.